Determination of organisational essential needs as the basis for developing a maṣlaḥah-based performance measurement - Achmad Firdaus (ISRA International Journal of Islamic Finance, 2021)
Purpose - The purpose of the study is twofold: first, it is to develop each aspect of maṣlaḥah ḍarūriyah (essential needs), i.e. dīn (faith/religion), nafs (soul), ʿaql (intellect), naṣl (descendants) and mal (wealth), into various aspects of organisational essential needs; second, it is to formulate maṣlaḥah-based performance measurement. Design/methodology/approach - The research is an exploratory study that uses a two-stage design: defining the research question and developing the research design. The research question is how each element of maṣlaḥah ḍarūriyah can become an element of organisational essential needs. The research design developed is to formulate maṣlaḥah-based performance measurement. Findings - The study concludes that maṣlaḥah ḍarūriyah could be developed as a basis for identifying organisational essential needs. The five elements of maṣlaḥah ḍarūriyah are developed into the following organisational essential needs: worship orientation, internal process orientation, talent orientation, learning orientation, customer orientation and wealth orientation. Maṣlaḥah-based performance measurement uses five variables: strategic objective, measure, formula, target and strategic initiatives and applies the modified plan - do - check - action cycle: performance planning, performance implementation, performance evaluation and performance action. Practical implications - Organisational essential needs can be developed by Islamic financial institutions (IFIs) into performance measurement. IFIs have six essential needs that can be developed into performance variables. Key performance indicators that can be developed for each need are worship orientation (social responsibility, regulatory compliance and Sharīʿah compliance); internal process orientation (innovation process, digital adaptation and employee satisfaction); talent orientation (career development, talent pool, compensation and benefits); learning orientation (training programme, training evaluation and return on training investment); customer orientation (customer engagement, customer satisfaction, customer survey and promotion programme); wealth orientation (profitability, cost-cutting, share prices, dividends, cost efficiency and financial sustainability). Originality/value - This paper contributes to new knowledge. The study attempts to discuss the organisational essential needs based on the maṣlaḥah ḍarūriyah concept, while previous studies discussed organisational needs based on Maslow's hierarchy of needs. In developing performance measurement, organisational performance is measured in a balanced manner. According to the concept of maṣlaḥah, not only financial factors but also worship, internal processes, talents, learning and customers define organisational needs. Thus, organisational needs are considered not only in terms of material factors but also in terms of spiritual (worship) factors.
Keywords: 330; Human needs; Maṣlaḥah-based performance; Maṣlaḥah ḍarūriyah; Maṣlaḥah performa; Organisational essential needs